The Johns Hopkins Venous Thromboembolism Collaborative: Multidisciplinary team approach to achieve perfect prophylaxis. (December 2016) - Streiff, Michael B.; Lau, Brandyn D.; Hobson, Deborah B.; Kraus, Peggy S.; Shermock, Kenneth M.; Shaffer, Dauryne L.; Popoola, Victor O.; Aboagye, Jonathan K.; Farrow, Norma A.; Horn, Paula J.; Shihab, Hasan M.; Pronovost, Peter J.; et al.
Abstract : Venous thromboembolism (VTE) is an important cause of preventable harm in hospitalized patients. The critical steps in delivery of optimal VTE prevention care include (1) assessment of VTE and bleeding risk for each patient, (2) prescription of risk‐appropriate VTE prophylaxis, (3) administration of risk‐appropriate VTE prophylaxis in a patient‐centered manner, and (4) continuously monitoring outcomes to identify new opportunities for learning and performance improvement. To ensure that every hospitalized patient receives VTE prophylaxis consistent with their individual risk level and personal care preferences, we organized a multidisciplinary task force, the Johns Hopkins VTE Collaborative. To achieve the goal of perfect prophylaxis for every patient, we developed evidence‐based, specialty‐specific computerized clinical decision support VTE prophylaxis order sets that assist providers in ordering risk‐appropriate VTE prevention. We developed novel strategies to improve provider VTE prevention ordering practices including face‐to‐face performance reviews, pay for performance, and provider VTE scorecards. When we discovered that prescription of risk‐appropriate VTE prophylaxis does not ensure its administration, our multidisciplinary research team conducted in‐depth surveys of patients, nurses, and physicians to design a multidisciplinary patient‐centered educational intervention to eliminate missed doses of pharmacologic VTE prophylaxis that has been funded by the Patient Centered Outcomes Research Institute. We expect that the studies currently underway will bring us closer to the goal of perfect VTE prevention care for every patient. Our learning journey to eliminate harm from VTE can be applied to other types of harm. Journal of Hospital Medicine 2016;11:S8–S14. © 2016 Society of Hospital Medicine